FOOD AND FEEDING HABITS OF PENAEUS SEMISULCATUS DE HAAN AT MANDAPAM - Thomas, M M (Indian Journal of Fisheries, 2011)
Penaeus semisulcatus feed on a variety of food items viz., polyohaetes, crustaceans, molloiscs diatoms, foraminiferEns and radiolarians, eventhough, detritus and sand formed bulk of the stpmaoh contents. There was marked difference in the food composition of the species from the Palk Bay and Gulf of Mannar. Actively fed prawns were found to be more in the night catches. The species do not exhibit preference to any particular food itÂ«m. It is concluded that the abundance of a particular food item was dependent on its availability during the season when they are predominent. There was no significant difference in the food and fee^ding habits in the various size groups